Growth parameters estimates of Maurolicus stehmanni Parin & Kobyliansky 1996 (Teleostei, Sternoptichydae) from south and southeastern Brazilian waters (Brazilian Journal of Oceanography, 2004)
This paper on the otolith microstructure analysis of Maurolicus stehmanni presents estimates of the species growth parameters and longevity. The species inhabits the outer shelf and slope of the southern and southeastern Brazilian Exclusive Economic Zone (EEZ). Growth parameters are important for the knowledge of the species' life history and rational management. M. stehmanni constitutes an important link between the initial and final components of the alimentary chain of the open sea ecosystem, being one of the main food items for squids and large pelagic fish. Among the various applied methods those which presented the most coherent values for growth parameters and were best adapted to the von Bertallanfy's equation were: Li= 55mm K= 0.0088/day and to= 5.5 days Maurolicus stehmanni's longevity is of less than one year (around 220 days) and the sagita daily otolith rings are useful for the determination of its age.